2022
DOI: 10.1088/1742-6596/2214/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence generated solar farside magnetogram using conditional generative adversarial network

Abstract: A solar flare occurs due to a magnetic field reconnection above the active region. The active region magnetic complexity observed in the magnetogram could be used as proxies for solar flare forecasting. It is also known that solar flares that occur from emerging active regions located near the solar disk eastern limb can still have an impact on the Earth. Therefore, magnetic observation of active regions in the solar farside is important to forecast east limb flares occurrences. This study utilizes the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Ugarte-Urra et al (2015) showed that integrated 304 Å light curves can be used as a proxy for the TUMF of the AR. Based on these results, several studies tried to generate solar magnetograms from the EUV 304 Å images using deep learning (Alshehhi 2020;Dani et al 2022). J20 generated more realistic magnetograms using the EUV 304, 193, and 171 Å images.…”
Section: Generation Of Solar Farside Magnetogramsmentioning
confidence: 99%
“…Ugarte-Urra et al (2015) showed that integrated 304 Å light curves can be used as a proxy for the TUMF of the AR. Based on these results, several studies tried to generate solar magnetograms from the EUV 304 Å images using deep learning (Alshehhi 2020;Dani et al 2022). J20 generated more realistic magnetograms using the EUV 304, 193, and 171 Å images.…”
Section: Generation Of Solar Farside Magnetogramsmentioning
confidence: 99%
“…The general idea of generating synthetic images is not new and has been improving dramatically over the years, including for tackling class imbalance in various domains such as medical applications (Frid-Adar et al 2018 (Xu et al 2019;Li et al 2021). So far, previous work on space weather image synthesis has focused on converting SDO/AIA imagery to SDO/HMI imagery (Dani et al 2022;Sun et al 2022), or vice versa (Dash et al 2022), and mapping SDO/AIA images to corresponding images with different extreme-ultraviolet channels (Salvatelli et al 2022). Such image-to-image translation is a class of computer vision tasks that typically involves learning a mapping function between the two domains, such that the output image preserves the content and key features of the input image.…”
Section: Introductionmentioning
confidence: 99%